Against labor : how U.S. employers organized to defeat union activism - Feurer, Rosemary; Pearson, Chad (Working class in American history., 2017)
Against labor highlights the amazingly successful efforts by employers to control workers while simultaneously shaping themselves into a new class. Ranging across a spectrum of understudied issues, essayists explore employer anti-labor strategies and offer incisive portraits of companies that aggressively opposed unionization. Other contributors examine the anti-labor movement against a backdrop of larger forces, such as the intersection of race and ethnicity with anti-labor activity, and anti-unionism in the context of neoliberalism. A timely and revealing collection, Against labor deepens our understanding of management history and employer activism and their metamorphic effects on the American workplace. --Cover.